ANTESEDEN DAN KONSEKUENSI AUDIT DELAY TERHADAP KUALITAS AUDIT - Suyanto Suyanto; Nur Anita Chandra Putry; Elysabet Sugiharti (AKUNTANSI DEWANTARA, 2018)
This study aimed to examine the variable of firm size and audit opinion whether the two variables are antecedent variable from audit delay and influence to audit quality. This study uses secondary data in the form of annual financial statements (annual report) company. The population in this study are all manufacturing companies in basic and chemical industry sectors that have been listed in Indonesia Stock Exchange (BEI). The sample in this research is manufacturing company of industrial sector of basic material and chemical observation that meet the criteria and has been determined related to the problem. Sampling technique that will be used in this research is purposive sampling technique. Technique analysis data in this research is by using method of Structural Equation Model - Partial Least Square (SEM-PLS) with WarpPLS. Based on the result of data analysis and the result of hypothesis testing, it is concluded that firm size and audit opinion are antecedents of audit delay while audit quality is not a consequence of audit delay.